Histological changes in periodontal tissue caused by the application of citric acid in the treatment of periodontal disease - Nedeljković Ružica; Bojić Petar; Zelić Obrad (Serbian Medical Society - Dental Section, Belgrade, 2007)
Introduction: Surface conditioning of teeth with periodontal disease in the surgical treatment of periodontal disease has an important role in the reparation of periodontal tissue. The aim of this study was to evaluate histologically the effect of citric acid on the induction of connective tissue attachment, i.e. cementogenesis and the resorption of cementum and dentin after flap reposition on the exposed tooth surfaces. Materials and Methods: The study was conducted on 12 "White Landras" pigs, 6 male and 6 female, with deciduous dentition. The "split mouth" technique was used for more adequate assessment and comparison of data. Exposed surfaces of the upper left canine were treated with laterally positioned flap (LPF) and their counterparts with free gingival graft (FGG). The recipient site was prepared by tissue excision and the tooth surface was prepared using hand instruments. The donor site for LPF was the edentulous region lateral to the treated tooth, where the full width flap was lifted to completely cover the exposed root surface over the enamel-cementum junction. In the experimental group, a fresh solution of citric acid (pH=1) was applied for 3-5 min with a sterile cotton pellet prior to the flap reposition. The tooth was rinsed with saline and the wound was sutured with single sutures. In the control group, the identical surgical treatment was performed but without citric acid. FGG, i.e. half width flap taken from the edentulous region lateral to the treated teeth, was used to cover the exposed tooth surfaces. Prior to FGG positioning in the experimental group, citric acid was applied in the same manner as in animals treated with LPF. The graft covered the exposed root surface. Fixation was done with single sutures and the wound was additionally preserved with surgical dressing. The control group was treated without citric acid. The animals were sacrificed eight weeks after the treatment. The material was prepared in a routine manner for histological sampling under light microscopy. After 10% formalin fixation, the material was decalcified for 7-10 days. Paraffin molds were cut in 5 μm thick slices which were stained with haematoxylin eosin (HE), Masson-Trichrome and Paf-Hallmi. Periodontal tissue status in experimental animals was analyzed under the light microscope. Results: Citric acid applied on the exposed tooth surface during the flap surgery had a positive effect on cementogenesis. Cementoblasts were observed along root cementum in thick rows. Newly formed cementum was hyperplastic, with regular laminar structure and more evident on animal models treated with full width flap. No damage of odontoblasts or pulpal connective tissue was observed.